Depressive response in children with insulin-dependent diabetes - Laghouat schools as a model - - Oum ennoune CHLAOUCHI; Samia ARAR (Social Sciences Journal, 1970)
The study in hands aims to identify the depressive responsiveness of type 1 diabeticchildren, through recognizing their physical, psychological and neurological environment; inaddition to their behavioral and Gnostic environment. Therefore, the researcher attentivelyselected a sample of 04 children to do a legalized interview with their teachers including aT.A.T test. As a result of the study, children have a depressive responsiveness embodied inphysical, psychological, neurological, Gnostic and behavioral effects.